History of music - Akin, Pearle (My University, 1905)
Introduction: Music is an art which employs sounds as a medium of artistic expression for what is not of painting, of acting, or ward feelings of which all In the matter of in the province of literature, of sculpture, of architecture. Music embodies the in - those other arts can but exhibit the effect expression, architecture may be compared with music in the earlier stages of its development, since representing and also prompting a general idea of solemnity or grandeur, or gaiety; but music left architecture far behind when, in later times, it assumed the power of special individual, and personal utterance of every variety of passion. The indefiniteness of musical expression furnishes no argument that music is inexpressive, but is one of the qualities that place it on the highest level of art excellence, enabling it to suggest still more than it displays, and to stimulate the imagination of the witness as much as to exercise that of the artist. It is common to style music "the universal language"; but the definition is untrue, for in every age and in every clime there are varieties of musical idiom which are unsympathetic, if not unintelligible, to other generations than those among whom they are first current, and, still more the very principles that govern it have been and are so variously developed in different times and places that music which is delightful at one period or to one people is repugnant at another epoch or to a different community. The earlier forms of music were very simple, the range of tones employed was narrow, and the habits of mind in the people employing them apparently calm and almost inactive. As time passed on more and more tones were added to the musical scales, and more and more complicated relations recognized between them, and the music thereby became more diversified in its tonal effects, and therein better adapted for the expression of a more energetic or more sensitive action of mind and feeling.
Citation: Akin, Pearle. History of music. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Ancient and Modern History of Music; Egypt - 4000 B.C.; XXth dynasty - 1300 B.C.; Theses